Sokasi Commodity Production: The Utilization of Bamboo Stem Fiber Composite to Create Balinese Local Products - Wigraha, Nyoman Arya; Djoko Kustono; Tuwoso; Dwi Agus Sudjimat (Universitas Pendidikan Ganesha, 2024)
This research aims to determine the optimal combination of a mixture containing bamboo fibre and polyester resin, with the addition of coconut fibre as a reinforcing material. The main objective of this research is to test tensile tests to determine the most suitable strength factor. In addition, this research aims to evaluate how changes in specific parameters affect the tensile characteristics of composite materials. The parameters observed include the proportion of the matrix to the volume of coconut fibre, the percentage of alkali concentration, and the length of the coconut fibre. The composite fabrication stage involves using the hand lay-up and Taguchi methods. The reason for choosing the L4(23) orthogonal experimental design is that there are three process parameters, each with two levels. The trial was duplicated five times. Important factors studied include the ratio of matrix and volume of coconut fibre, alkali concentration, and length of coconut fibre. Based on the results obtained from this research, it has been proven that the most effective combination to achieve the highest tensile strength is a matrix that accounts for 60% of the composition, coconut fibre occupies 20% of the volume, and an alkali concentration of 5.%, and coconut fibre strands measuring 30 mm long. The tensile strength test result of this particular composition was 54.34 MPa. Apart from that, the length of coconut fibre is the most significant factor in increasing tensile strength, with a contribution of 42.560%.